Spectroscopic studies of sodium nitrate plasma produced by nanosecond laser ablation. Issue 3 (3rd March 2016) - Salik, M.; Hanif, M.; Wang, J.; Zhang, X. Q.
ABSTRACT: We present the optical emission characteristics of the sodium plasma produced at the surface of sodium nitrate (NaNO3 ) also known as Chile saltpeter. We used a Q-switched Nd:YAG (Quantel Brilliant) pulsed laser having a pulse duration of 5 ns and 10 Hz repetition rate which is capable of delivering 400 mJ at 1064 nm and 200 mJ at 532 nm. The target material was placed in front of laser beam in air (atmospheric pressure). The experimentally observed line profiles of neutral sodium have been used to extract the electron temperature using the Boltzmann plot method, whereas the electron number density has been determined from the Stark broadening. The electron temperature is calculated by varying the distance from the target surface along the line of propagation of the plasma plume and also by varying the laser irradiance. Besides, we have studied the variation of number density as a function of laser irradiance as well as its variation with the distance from the target surface. It is observed that electron temperature and electron number density increase as the laser irradiance is increased.